2018
DOI: 10.1021/acs.molpharmaceut.8b00654
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Transporter-Mediated and Passive Hepatic Uptake Clearance Using Rifamycin-SV as a Pan-Inhibitor of Active Uptake

Abstract: The use of in vitro data for the quantitative prediction of transporter-mediated clearance is critical. Central to this evaluation is the use of hepatocytes, since they contain the full complement of transporters and metabolic enzymes. In general, uptake clearance (CL) is evaluated by measuring the appearance of compound in the cell. Passive clearance (CL) is often determined by conducting parallel studies at 4 °C or by attempting to saturate uptake pathways. Both approaches have their limitations. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
(86 reference statements)
2
8
0
Order By: Relevance
“…Given the importance of uptake transporters, it has become increasingly common practice to assess new molecular entities (NMEs) as liver transporter substrates in vitro using various combinations of human SLC-transfected cells and primary human hepatocytes. For the latter, studies have suggested that one can differentiate total active uptake (vs. passive) by incubating a high concentration of a pan-SLC inhibitor, such as rifamycin SV (∼1 mM), or comparing uptake rates at 37°C versus 4°C (Bi et al, 2017;Chothe et al, 2018). However, due to the limitation of selective inhibitors, assessing individual SLC activity in human hepatocytes has proven to be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of uptake transporters, it has become increasingly common practice to assess new molecular entities (NMEs) as liver transporter substrates in vitro using various combinations of human SLC-transfected cells and primary human hepatocytes. For the latter, studies have suggested that one can differentiate total active uptake (vs. passive) by incubating a high concentration of a pan-SLC inhibitor, such as rifamycin SV (∼1 mM), or comparing uptake rates at 37°C versus 4°C (Bi et al, 2017;Chothe et al, 2018). However, due to the limitation of selective inhibitors, assessing individual SLC activity in human hepatocytes has proven to be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion drawn from this work is not affected by this error. The authors regret this error and deeply apologize for any inconvenience that may have been brought to the readers. …”
mentioning
confidence: 99%
“…Uptake as the RDS in Pevonedistat Hepatic Clearance the uptake of pevonedistat was investigated at 37 C, 4 C and in the presence of selective inhibitors of major liver uptake transporters and a pan-inhibitor (1 mM of rifamycin SV) (Chothe et al, 2018). The uptake of pevonedistat was temperature-dependent and sodium-independent.…”
Section: Discussionmentioning
confidence: 99%
“…The total uptake of pevonedistat into hepatocytes was measured for 1, 2, 3, 5, 7, and 10 minutes at 37 C. Similarly, the uptake via passive diffusion into hepatocytes was measured at 1 lM for 1, 2, 3, 5, 7, and 10 minutes at 4 C. For inhibition studies, hepatocytes were pre-incubated with an inhibitor for 15 minutes and then co-incubated with an inhibitor and [ 14 C]pevonedistat or a probe substrate for 5 minutes in KHB buffer at 37 C. Rifamycin SV (20 lM), cyclosporine A (CsA, 20 lM), verapamil (300 lM), ketoprofen (300 lM), and nitrobenzylthioinosine (NBMPR, 10 lM) were used as inhibitors for organic anion-transporting polypeptides (OATPs), Na 1 -taurocholate co-transporting polypeptide (NTCP) (in addition to OATPs), organic cation transporter (OCT) 1 (also inhibits P-gp), organic anion transporter (OAT) 2, and equilibrative nucleoside transporter (ENT) 1, respectively. We also included rifamycin SV at 1 mM as a pan-inhibitor, which has been shown to inhibit all six major uptake transporters (OATP1B1, OATP1B3, OATP2B1, NTCP, OCT1, and OAT2) (Chothe et al, 2018;Bi et al, 2019). For uptake kinetic experiments, hepatocytes were incubated with pevonedistat at various concentrations (0.27 to 200 lM, [ 14 C]pevonedistat 1 cold pevonedistat) for 5 minutes.…”
Section: Downloaded Frommentioning
confidence: 99%